PENGUATAN KOMPETENSI PENGELOLA PERPUSTAKAAN MADRASAH DAN SEKOLAH MELALUI DIKLAT BERKESINAMBUNGAN - Inda Fitri; Mega Orina Fitri; Zulvia Trinova (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
Education and training for madrasah and school library managers in the city of Padang to manage existinglibraries should have an educational background in Library Science. In fact, the head of the library is ateacher in the field of study and the library manager is still honorary. Lack of attention from the leadershipso that library managers are not creative because there is no continuous education and training. Thequestionnaire was distributed by the service team to 74 schools and madrasahs in the city of Padang andonly 30 returned questionnaires, where the average school library accreditation score was very low andbelow the standard value of accreditation issued by the Jakarta National Library. This research-basedservice method is Participation Action Research (PAR) which involves parties from the Head of the WestSumatra Provincial Education Office, West Sumatra Provincial Archives and Libraries, the Head of theMinistry of Religion of Padang City is invited as a speaker. From the results of the education and trainingactivities, it is not clear that the policies that will be carried out by leaders and decision makers to advancethe library in a better direction.